Waste-to-Energy in Saudi Arabia: Treatment of petroleum wastewaters utilizing zeolite structures in the removal of phenol pollutants by using the power of molecular dynamics method. (March 2023) - Melaibari, Ammar A.; Elamoudi, Ahmed S.; Mostafa, Mohamed E.; Abu-Hamdeh, Nidal H.
Abstract: Today, the lack of water resources on the one hand and the pollution of surface water by industrial wastewater on the other hand have become a big challenge. One of the pollutants of water resources is phenol, which enters the environment from the wastewater of various industries such as petrochemical, refinery, pharmaceutical, etc. Due to its toxicity, high stability, ability to dissolve in water, etc., this compound has caused many problems and it is necessary to remove it from the petroleum industry effluent using modern methods to remove phenol. In this regard, in this work, the removal of phenol molecules from the aqueous environment using zeolites has been investigated by using the power of molecular dynamics (MD) method to study the intermolecular interactions. According to the obtained results, ZnO zeolite has been introduced as the best adsorbent with the highest interaction with phenol and also the stable adsorption of phenol molecules. In fact, this work has provided an efficient material for the treatment of petroleum wastewaters and paves the way for the use of these materials in the removal of phenol from petroleum wastewaters specially in Saudi Arabia.